THE POLITICAL ROLE OF THE ORTHODOX CLERGY IN THE UNION OF THE ROMANIAN PRINCIPALITIES (1859) - BOICU, Dragoș (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2022)
The union of the Romanian Principalities was a decisive moment in the history and evolution of the modern Romanian state, but its realization cannot be separated from the actions of the bishops and clergy, who were co-opted in the electoral process from the very beginning. The activity of the clergy was not strictly limited to the bureaucratic management of the elections but revealed a set of political beliefs, actively supporting the idea of Romanians’ national unity. This paper aims to insist on the political partisanship of the clergy respectively, on the immediate consequences of their involvement in political life.